Peran dan Tantangan Perempuan dalam Kepemimpinan Desa: Analisis di Kecamatan Gunung Raya, Kabupaten Kerinci - Nanik Mandasari; Eka Septiani (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Women's leadership at the village level is increasingly a concern, especially in developing countries such as Indonesia, where patriarchal cultures often limit women's roles. This study aims to analyze the roles and challenges of women in village leadership in Gunung Raya District, Kerinci Regency. The theories used include gender equality theory, feminism, transformational leadership, and dual role theory. The method used is qualitative research with a case study approach, involving in-depth interviews, observations, and documentation. The results of the study show that women village heads have a significant role in decision-making and community empowerment, but they are faced with the challenges of patriarchal culture, resistance from the apparatus, and the pressure of dual roles. In conclusion, despite the challenges, women village heads are able to overcome these barriers with inclusive leadership strategies and increased social capital, strengthening their capacity as effective leaders. Support from the government and the community is urgently needed to encourage women's involvement in local politics.